Strengthening the legal framework for the right to healthcare services in underdeveloped regions: A study in East Nusa Tenggara - Charles G.R. Banoet; Moh. Fadli; Istislam Istislam; Riana Susmayanti (International Review of Social Sciences Research, 2026)
The provision of health services in underdeveloped regions is still facing challenges related to the fulfilment of the right to safe, quality and affordable health services being guaranteed by the 1945 Constitution of the Republic of Indonesia and Law Number 17 of 2023 on Health. This study is aimed to characterize the legal regulation concerning fulfilment of the community right to health service in East Nusa Tenggara Province as one of the underdeveloped regions. The methods employed in this study are normative legal methods using a statutory, conceptual, philosophical, case, and comparative approach which is prescriptive in nature. The analysis uses welfare state theory and states’ obligation to fulfil or realize socio-economic rights to assess the effectiveness of legal regulations of the health sector. As per the results of the study, the right to safe, quality, and affordable health service is recognized in Law Number 17 Year 2023 on Health. But this law has not yet provided a clear and operational normative formulation about the standard of fulfillment of this right, especially in underdeveloped regions. The ambiguity of the norm can lead to implementation gaps like lack of health facilities and infrastructure, shortage of health workers, disparity in quality of services, and low accessibility and affordability of services. Consequently, the discussion stresses the need for the laws to be strengthened by formulating more measurable normative standards, affirmative regulations for underdeveloped regions, more stringent supervision and accountability of the state to implement the right to healthcare services fairly and sustainably.